Assessing The Feasibility of a Web-Based Interactive Writing Assessment (WISSE): An Evaluation of Media and Linguistic Aspects - Hamamah; Rafidah Sahar; Ive Emaliana; Yulia Hapsari; Putu Dian Danayanti Degeng (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2023)
This study aims to conduct a feasibility test on a Web-Based Interactive Writing Assessment (WISSE) that has been designed to assist students and teachers of Academic Writing classes by facilitating feedback provision online. WISSE was created to align with the requirements of the OBE curriculum. During this study, feedback about WISSE was gathered to enhance its feasibility and readiness. Trials focused on evaluating media aspects (usability, functionality, visual communication) and linguistic aspects (technical language, grammar, word choice). Quantitative and qualitative data were employed. The quantitative data were obtained through a material validation questionnaire and media validation using a rating scale on the quality of the media obtained from the objective assessment of media experts and linguists. The qualitative data were obtained from the feedback of media experts and linguists on the quality of the media provided in the comment column on the questionnaire. This data serves as a consideration in revising the product for the website’s view and feasibility. the results of the expert test indicate that the web-based interactive learning assessment product, WISSE, is feasible for use, although revisions based on feedback from media and language experts are necessary before piloting it to a wider audience.